Large electrocaloric response and energy storage study in environmentally friendly (1 − x)K0.5Na0.5NbO3–xLaNbO3 nanocrystalline ceramics. Issue 12 (27th September 2018) - Kumar, Raju; Kumar, Ashish; Singh, Satyendra
Abstract : An electrocaloric material with a negative and positive electrocaloric effect (ECE) is identified to be a high potential candidate for solid-state refrigeration technology due to a changing dipolar entropy under a varying electric field. Abstract : An electrocaloric material with a negative and positive electrocaloric effect (ECE) is identified to be a high potential candidate for solid-state refrigeration technology due to a changing dipolar entropy under a varying electric field. We have experimentally observed large values of negative and positive electrocaloric (EC) response in environmentally friendly (1 − x )K0.5 Na0.5 NbO3 – x LaNbO3 ceramics using Maxwell's relationships. The maximum value of negative and positive ECE were found to be −0.88 K and 2.08 K at 50 kV cm −1 for x = 0.03. The material displays a high electrocaloric responsivity (−1.76 and 4.16 × 10 −7 K m V −1 for negative and positive ECE, respectively), COP (4.16) and energy storage capacity (0.17 J cm −3 ) for x = 0.03. The large values of negative and positive ECE, high values of electrocaloric responsivity, COP and energy storage capacity make this compound a good candidate for electrocaloric refrigeration and high energy storage applications. The Olsen cycle is discussed to explain the process involved in using this material for electrocaloric refrigeration.